Transverse relaxation rates of pulmonary dissolved-phase Hyperpolarized (129)Xe as a biomarker of lung injury in idiopathic pulmonary fibrosis - Kammerman, Jeff (Magn Reson Med, 2020)
PURPOSE: The MR properties (chemical shifts and R(2)* decay rates) of dissolved-phase hyperpolarized (HP) (129)Xe are confounded by the large magnetic field inhomogeneity present in the lung. This work improves measurements of these properties using a model-based image reconstruction to characterize the R(2)* decay rates of dissolved-phase HP (129)Xe in healthy subjects and patients with idiopathic pulmonary fibrosis (IPF). METHODS: Whole lung MRS and 3D radial MRI with four gradient echoes were performed after inhalation of HP (129)Xe in healthy subjects and patients with IPF. A model-based image reconstruction formulated as a regularized optimization problem was solved iteratively to measure regional signal intensity in the gas, barrier, and red blood cell (RBC) compartments, while simultaneously measuring their chemical shifts and R(2)* decay rates. RESULTS: The estimation of spectral properties reduced artifacts in images of HP (129)Xe in the gas, barrier, and RBC compartments and improved image SNR by over 20%. R(2)* decay rates of the RBC and barrier compartments were lower in patients with IPF compared to healthy subjects (P < 0.001 and P=0.005, respectively) and correlated to DL(CO) (R=0.71 and 0.64, respectively). Chemical shift of the RBC component measured with whole lung spectroscopy was significantly different between IPF and normal subjects (P = 0.022). CONCLUSION: Estimates for R(2)* in both barrier and RBC dissolved-phase HP (129)Xe compartments using a regional signal model improved image quality for dissolved phase images and provided additional biomarkers of lung injury in IPF.